Development of Character Education Based on School Culture in Non-Formal Education - Dadan Darmawan; Ila Rosmilawati; Herlina Siregar (Universitas Sultan Ageng Tirtayasa, 2022)
The study of character education is done at 5 (five) education units of non-formal education in Banten Provinces, Indonesia. This study aimed to find out the development of character education based on school culture on non-formal equivalent education units. The data collectiion technique of this study are interviews, observations, and documentation. The results of this ethnographic study is being developed to create a conceptual model of character education based on school community’s culture. The development of character education based on school culture at non-formal equivalent education units has outcomes such as: 1) determine the values of characters, 2) Determining the activity to develop character values, which are: a) Independence, b) self-authority, c) interest-based learning, locality, and d) sense of family. Character education through the school culture development is designed in 4 forms of activity which are a) routine activities, b) spontaneous activities, c) exemplary activities, and d) conditioning activities. Action education character program based on school culture can be done with home visit, donation for disaster, leadership training. Character education assessment based on school culture is done based on the behavior indicators from character values from activities which had been determined by the school. One of the evaluating techniques used are observation, an evaluation done through direct surveillance of the students. Although all school activities comprise of character values, it still must be exposed explicitly and must be reflected then confirmed at the end of each activity so the students are aware and understand